Case reportMyocardial infarction complicated by acute heart failure treated with percutaneous coronary intervention by transradial approach - Krynicki, Romuald; Sobocińska, Agnieszka (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
The early period of myocardial infarction may be a dramatic step in coronary heart disease due to the risk of sudden death or acute heart failure less often. It is known that a quick opening coronary artery responsible for the creation of a myocardial infarction, is the best method of treatment in the prevention of these complications. We describe a case of a 75-year-old patient with myocardial infarction complicated by pulmonary edema and cardiogenic shock, treated with primary coronary angioplasty with the left transradial approach.